De Novo Deletion of Chromosome 20q13.33 in a Patient with Tracheo-esophageal Fistula, Cardiac Defects and Genitourinary Anomalies Implicates GTPBP5 as a Candidate Gene - Solomon, Benjamin D (Wiley Subscription Services, Inc., A Wiley Company, 2011)
BACKGROUND: Tracheo-esophageal fistula (TEF) with/or without esophageal atresia (EA) is a common congenital malformation that is often accompanied by other anomalies. The causes of this condition are thought to be heterogeneous but are overall not well understood. CASE REPORT: We identified a patient with a TEF/EA, as well as cardiac and genitourinary anomalies, who was found to have a 0.7 Mb de novo deletion of chromosome 20q13.33. One gene within the deleted interval, GTPBP5, is of particular interest as a candidate gene. CONCLUSIONS: GTPBP5 bears further study as a cause of TEF/EA accompanied by other malformations. Birth Defects Research (Part A) 2011. © 2011 Wiley-Liss, Inc.